Creep analysis in reinforced concrete structures - Palomino Tamayo, Jorge Luis (2005)
The present report focuses on the behaviour of reinforced concrete structures under loads maintained constant in tinte. A procedure for combining linear short-time behaviour of concrete with nonlinear and linear creep functions is presented for analyzing plane franle structures. Creep produces stresses and strains redistribution over time in a reinforced concrete cross- section. In the case of statically indeterminate structures, this redistribution produces a variation in the final force diagrams. Also, creep relaxes induced stresses by a movement of a support with time as it is shown later. In comon structures, creep is more related to the control of defiexions, however. For that reason, some typical structures were analyzed by using a simplified and step-step method proposed by Ghali & Favre. The results show that there is not significance change in the final force diagrams of the structures in question. Nevertheless, it is appreciated that the deflexion in the middle section of a simple beam increases up to 4 times in 5 years. Meanwhile, these deflexions were compared with those obtained with formulas supported by American Concrete Institute (ACI) and Committee European of Concrete (CEB) finding results of the same order of magnitude. As a result, Branson formula was found to be more accurate although it simply considers steel ratio in compression. Other numerical studies show that columns with Steel minimum ratio equal to 1% could achieve fluency of steel under high stresses and that columns with steel ratios as high as 6%, the stresses carried by steel increases approximately 80% in 30 years while concrete compressive stresses reduces approximately 40% for columns under pure compression and 50% for beams subjected to bending moment or to a conibined action.